Understanding of Consent and Legal Rights Among Patients Undergoing Surgical Procedures, Medical & Paramedical Students and Paramedical staff in tertiary care hospitals. - Kumari, Ishita; Samar, Akshita; Khullar, Keryn; Kaura, Mahika; Kumar, Tejaswi; Rajput, Kartik; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Informed consent is a cornerstone of ethical medical practice. Despite its legal and ethical importance, the understanding of consent and patient rights remains inconsistent among patients and healthcare providers in developing healthcare settings. Objective: To assess and compare the level of understanding of informed consent and legal rights among surgical patients, medical students, nursing students, and paramedical staff in two tertiary care hospitals .Methods: A cross-sectional descriptive study was conducted among 250 participants — 50 surgical patients, 100 medical students, 50 nursing students, and 50 paramedical staff (including nurses and technicians) — from two tertiary care hospitals attached to medical colleges. A structured, validated questionnaire assessed knowledge, attitude, and practices regarding consent and legal rights. Data were analyzed using descriptive statistics and chi-square tests. Results: Only 40% of surgical patients had a clear understanding of informed consent, compared to 82% of medical students, 76% of nursing students, and 65% of paramedical staff. Awareness regarding the legal implications of non-consensual procedures was highest among final-year medical students (90%) and lowest among patients (22%). Significant gaps were found between theoretical understanding and practical application among healthcare trainees. Conclusion: The study highlights inadequate understanding of consent and legal rights, particularly among patients and some paramedical staff. There is a pressing need for enhanced education on medical law, ethics, and patient rights across all tiers of healthcare delivery.